2020
DOI: 10.1111/trf.15713
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing O‐negative RBC utilization using a data‐driven approach

Abstract: BACKGROUND O‐negative red blood cells (ON‐RBC) are a precious resource and the international blood banking community has become increasingly concerned with its inappropriate utilization. AABB recently made several recommendations to address the issue. Solutions must be multifaceted and involve donor centers, blood banks, and clinical departments. From the perspective of a hospital blood bank, it is difficult to rely solely on increased donor recruitment and ubiquitous blood typing of the entire in‐patient popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“… RBC age: Days to irradiation from collection date Days from expiry (DFE): Subtracting transfusion date from the expiration date[ 10 ] Late transfusions: Units transfused in the past 2 weeks of RBC's shelf-life Percentage of irradiated RBC issued out of the group Percentage of irradiated RBC issued for nonhemato-oncology patients. …”
Section: Methodsmentioning
confidence: 99%
“… RBC age: Days to irradiation from collection date Days from expiry (DFE): Subtracting transfusion date from the expiration date[ 10 ] Late transfusions: Units transfused in the past 2 weeks of RBC's shelf-life Percentage of irradiated RBC issued out of the group Percentage of irradiated RBC issued for nonhemato-oncology patients. …”
Section: Methodsmentioning
confidence: 99%
“…By far, the most common reason for issuing an O RhD-negative unit to a non-O RhD-negative patient was inventory management: A third (33%) of all O RhD-negative units issued to non-O RhD-negative patients were issued purely to prevent outdating, mostly for non-urgent care in regular hospital wards. Other studies have also identified inventory management as a frequent cause of unnecessary use of O RhD-negative RBCs [2,3,5,7]. Understandably, to ensure patient safety in a country where geographical distances are a major issue, many remote blood banks wish to stock enough O RhD-negative units.…”
Section: Non-urgent Transfusions To Non-o Rhd-negative Patientsmentioning
confidence: 99%
“…Worldwide, the use of red blood cells (RBCs) is decreasing as clinicians increasingly adopt patient blood management principles and follow restrictive transfusion guidelines. Simultaneously, demand for O RhD-negative units has increased, and the proportion of transfused O RhD-negative units is generally up to twice as high as the proportion of the O RhD-negative blood group in the population [1][2][3][4][5]. Problems in recruiting enough O RhD-negative donors from an ageing donor population are universal, and the overutilization of O RhD-negative RBCs leads to supply shortages [3] and ultimately to situations where O RhD-negative RBCs are not available to patients who need them [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations